Factors Associated with Public Transportation Drivers’ Compliance with Smoke-Free Area Regulations at Depok City Terminal - Ihyani Nurdiena Marliamara; Tri Krianto; yaya, Dien Anshari; yaya, Faika Rachmawati; yaya, Puji Lestari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Smoking remains one of the most significant public health challenges in Indonesia, with serious impacts on mortality rates, economic burden, and low compliance with Smoke-Free Area policies. This study aimed to analyze factors associated with public transportation drivers’ compliance with Smoke-Free Area (SFA) regulations at the Depok City Terminal in 2024. This study employed a descriptive method with a quantitative approach and a cross-sectional design. The respondents consisted of 94 public transportation drivers selected using purposive sampling. Data were collected through a structured questionnaire covering individual characteristics as well as smoking attitudes and behaviors. Data analysis was conducted using the Chi-square test. The results showed that the majority of public transportation drivers (79.8%) were non-compliant with SFA regulations, while only 20.2% were compliant. Predisposing factors were significantly associated with drivers’ compliance (p-value < 0.05), as were enabling factors. However, the reinforcing factor, namely cigarette price, was not significantly associated with compliance. Keywords: Compliance, Public Transportation Drivers, Smoke-Free Areas